(untitled) (Asian Journal of Pharmaceutics (AJP), 2015)
One of the major factors affecting oral drug bioavailability is the activity of intestinal transport proteins, particularly forÂ the drugs that undergo absorption by active transport mechanism. Many of the active pharmacological agents and theÂ excipients used in their formulation are reported to modulate the activity of these transporters thereby either enhancing orÂ decreasing the drug absorption and its systemic availability. These excipients are considered pharmacologically â€œinertâ€ andÂ have been used since years in pharmaceutical formulations. Appreciable interest is developing on the data demonstratingÂ the role of excipients in altering the drug absorption across the intestine. Careful selection of the excipients thus is veryÂ important. A correctly chosen excipient can enhance the drug bioavailability and thus its therapeutic efficacy withoutÂ increasing its dose. For locally acting drugs having systemic side effects, a proper excipient could lead to a decrease in itsÂ systemic absorption, thus reducing its side effects. This review focuses on the current findings of the excipients identifiedÂ to modulate the activity of transporters, their mechanism of modulating the transporterâ€™s activity and various formulation strategies using these excipients to enhance drug absorption. Key words: Cacoâ€2 cell monolayers, drug transport, intestinal transporters, pharmaceutical excipients